Training Critical Thinking Skills with Schoology in Nervous System Sub-Material: Profile, Validity and Student Response - Ary Marchellina; Nur Qomariyah (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2022)
In the 4.0 era, many students have an electronic device related to learning activities. Refer to the open questionnaire, 41.2% of students in SMAN 1 Puri Mojokerto feel that nervous system material is hard to understand due to the lack of learning media to proponent the learning process. Some difficult concepts need media to support teaching nervous system material for students. The development of technology support 4-C competence to apply in a learning activity. One of the competence is critical thinking skills. The purpose of this experiment is to develop learning media e-learning Schoology as valid and practical media. Followed up the reason, a learning media, e-learning Schoology is made using the IDI method (Instructional Development Institute), including three steps: define, design, and develop. In this media, there are some activities to help the students training their critical thinking by doing a pretest-posttest and discussion. The media also contain material of nervous system and some games to give motivation. The result of media validation is 96.67%, lesson plan validation score is 97.40%, pretest-posttest question validation is 95.37%, and the validation of students worksheets is 92.05%, the four components decided to have a perfect category (valid). The result of students responded that including 35 students of SMAN 1 Puri Mojokerto indicates the convenience of the media is 88.61% so e-learning Schoology is categorized as a practical media. After that, the implementation of this media is permitted, but this research does not do that. Keywords: e-learning, Schoology, nervous systems, critical thinking, validity, student response